Fredholm theory of Toeplitz operators on doubling Fock Hilbert spaces - Al-Qabani, Aamena; Hilberdink, Titus; Virtanen, Jani A. (MATHEMATICA SCANDINAVICA, 2020)
We study the Fredholm properties of Toeplitz operators acting on doubling Fock Hilbert spaces, and describe their essential spectra for bounded symbols of vanishing oscillation. We also compute the index of these Toeplitz operators in the special case when $φ (z) = \lvert {z}\rvert^{β }$ with $β >0$. Our work extends the recent results on Toeplitz operators on the standard weighted Fock spaces to the setting of doubling Fock spaces.